2018
DOI: 10.5539/ijbm.v14n1p180
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in the Healthcare Sector and the Important Role of Education and Training Activities: The Case of Regione Lombardia

Abstract: Purpose-Risk is intrinsically linked to all economic activity, and can never be completely eliminated; however, in certain cases and conditions, it can be mitigated. From the managerial perspective, it is possible to distinguish between speculative risks and pure risks. This distinction is made in relation to the effects produced from particular events on the economic conditions of the company. Speculative risks can lead to profits or losses, as they are connected to both unfavorable and favorable events, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The probability of an uncertain event occurring is often unknown, as are its consequences. In this case, it is more important to apply precautionary than preventive measures to protect against uncertainty (Capocchi, Orlandini, Pierotti, Luzzi & Minetti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The probability of an uncertain event occurring is often unknown, as are its consequences. In this case, it is more important to apply precautionary than preventive measures to protect against uncertainty (Capocchi, Orlandini, Pierotti, Luzzi & Minetti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Risk management (R.M.) in health care refers to a system that is made up of multiple procedures that are used to estimate, assess, and prevent risk to lessen the likelihood of unfavourable effects being had on a variety of factors, including technical and economic aspects (Alessandro et al, 2018). Wu et al (2015) opined that the likelihood of errors and adverse outcomes in healthcare systems could not be eliminated or reduced by implementing a recursive non-stop development process such as the Plan Inspires, Do, Check, and Act (PDCA) model.…”
Section: Introductionmentioning
confidence: 99%
“…A successful risk management program has various benefits, including ensuring compliance with safety standards, identifying deficiencies before an adverse event, minimizing loss after an incident, and enhancing safety to improve patient outcomes and reduce adverse event frequency, type, and severity (Abor & Abor, 2021) Alessandro et al (2018) identified education and training as crucial risk management practices in healthcare, while Pascarella et al (2021) emphasized the significance of a systematic risk management framework, including the use of a risk matrix, in healthcare organizations. Ferdosi et al (2020) recommended that healthcare organizations utilize an array of risk management techniques and tools that are adapted to their specific requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research conducted by Capocchi, Orlandini, Pierotti, Luzzi, and Minetti (2019) contributes to the knowledge related to riskmanagement policies in the healthcare sector. Based on the case study of Regione Lombardia, the research integrates the dimensions of organization and individuals with the cross-section of education and training in new risk-management systems.…”
Section: Introductionmentioning
confidence: 99%